Family Communication Problems in the Light of Verbal Violence - الشيخ, عفراء; ميرنا دلالة (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This research deals with the concept of violence and its forms and trends , and recognises its nature and its anthropological origin, and how the symbolic family violence affects social institutions. That is for the verbal violence differs in its meaning according to the family structure of the abused individuals, because what a family considers a verbal and symbolic violence may not be considered violent words by another . And that’s due to the different upbringing methods for the members of those families, which in turn reflects diversity in the degree of adaptation or rejection of the the symbolic and verbal violence practiced on them by those with violent upbringing methods . So, the verbal and symbolic and family violence is considered a very dangerous topic , especially when it is related to the violence practiced indoors , whivlch is a closed and hidden environment.